2018
DOI: 10.1089/end.2017.0538
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic In Situ Dismembered Pyeloplasty Can Facilitate Laparoscopic Ureteropelvic Junction Obstruction Repair: A Prospective Cohort Trial

Abstract: Laparoscopic in situ pyeloplasty is a safe and effective approach that can help simplify laparoscopic pyeloplasty, especially at teaching centers where surgeons with variable levels of experience perform laparoscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…12,13 CV was found in 17.18% of patients in our study and was seen predominantly on the left side and in female gender. Similarly, in Aminsharifi’ et al’s 14 study, 20 of 37 CV patients were girls, while 21 patients showed CV on the right side. In our study, patients without CVs presented more severe hydronephrosis than those with early diagnosis and mostly intrauterine diagnoses.…”
Section: Discussionmentioning
confidence: 68%
“…12,13 CV was found in 17.18% of patients in our study and was seen predominantly on the left side and in female gender. Similarly, in Aminsharifi’ et al’s 14 study, 20 of 37 CV patients were girls, while 21 patients showed CV on the right side. In our study, patients without CVs presented more severe hydronephrosis than those with early diagnosis and mostly intrauterine diagnoses.…”
Section: Discussionmentioning
confidence: 68%
“…The mean operative time for PUJ anastomosis was lesser in laparoscopic in situ pyeloplasty group. [ 14 ] This technique is similar to PAD technique described by Ahlawat et al . [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a few pediatric large se- Conversion to open procedure 0 (8). However, while early series had reported anastomotic stenosis in babies (9,10), subsequent studies demonstrated feasibility irrespective of patient age and weight (6,7,(11)(12)(13). LP has been thought to be a technically challenging procedure in children.…”
Section: Discussionmentioning
confidence: 99%
“…Through laparoscopic view, the PUJ is seen in its real position, in contrast to the open or video assisted procedure which brings the PUJ outside, disrupting its normal anatomy. LP is thought to provide better identification to anomalous vessels and avoid twisting or bad positioning of the ureter ( 3 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation